1999
DOI: 10.1093/ndt/14.suppl_1.55
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bcl-2 and bax in glomerular disease

Abstract: Bcl-2 may account in part for the maintenance of hypercellularity in human glomerular diseases through preventing cell death and by counteracting bax which may be expressed to regulate excessive proliferation. This process is associated with the effect of PDGF B-chain expression. Bax expression may be important in the cell loss leading to glomerulosclerosis and TGF-beta1 participates in this process by increasing bax expression. Thus, the balance of bcl-2/bax expression may be critical in the course of human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…Proliferative glomerulonephritis shows increased mitotic activity in glomeruli or infiltrating inflammatory cells. Thus, recovery of the lesions probably depends on increased apoptotic removal of these cells (4,17). Our results support this theory.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Proliferative glomerulonephritis shows increased mitotic activity in glomeruli or infiltrating inflammatory cells. Thus, recovery of the lesions probably depends on increased apoptotic removal of these cells (4,17). Our results support this theory.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the balance between them is critical for the progression of glomerular diseases. Bcl-2 expression correlates with proliferation/activation of mesangial cells (4,18,19). However, bax expression correlates with mesangial matrix expansion and type-IV collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis is associated with an increase in levels of proapoptotic proteins such as Bax and decrease in the levels of prosurvival proteins like Bcl-2 (23,52,68). In line with these observations, we observed that glucosamine (10 mM) produced a significant increase in Bax levels that was accompanied by a concomitant decrease in Bcl-2 protein levels and occurred after the increase in p53 levels (Fig.…”
Section: E216supporting
confidence: 86%